2018
DOI: 10.1021/acs.bioconjchem.8b00311
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid Surface Modified Liposomes Prepared via Orthogonal Aminoxy Coupling: Synthesis of Nontoxic Aminoxylipids Based on Symmetrically α-Branched Fatty Acids, Preparation of Liposomes by Microfluidic Mixing, and Targeting to Cancer Cells Expressing CD44

Abstract: New synthetic aminoxy lipids are designed and synthesized as building blocks for the formulation of functionalized nanoliposomes by microfluidization using a NanoAssemblr. Orthogonal binding of hyaluronic acid onto the outer surface of functionalized nanoliposomes via aminoxy coupling ( N-oxy ligation) is achieved at hemiacetal function of hyaluronic acid and the structure of hyaluronic acid-liposomes is visualized by transmission electron microscopy and cryotransmission electron microscopy. Observed structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…For instance, HA-coated cationic liposomes containing cabazitaxel (a tumor cell inhibitor) and silibinin (a CSC inhibitor), displayed enhanced cytotoxicity with low IC50, hampered cell migration, and triggered apoptosis among human prostate tumor cells with CD44 expression [147]. HA-coated nanoparticles containing anti-tumor drugs could also target CD44-positive cancer cells with high specialization and efficient drug delivery, refining the current anticancer management [148][149][150][151][152][153]. It has been observed that a rationally designed nanosystem containing gold nanostar/siRNA of heat shock protein 72/HA is endowed with the property of selectively sensitizing CD44-positive TNBC cells to hyperthermia, and improves the therapeutic accuracy and efficacy to TNBC with decreased unpleasant side effects both in vitro and in vivo [153].…”
Section: Cd44 and The Development Of Anti-tumor Drugsmentioning
confidence: 99%
“…For instance, HA-coated cationic liposomes containing cabazitaxel (a tumor cell inhibitor) and silibinin (a CSC inhibitor), displayed enhanced cytotoxicity with low IC50, hampered cell migration, and triggered apoptosis among human prostate tumor cells with CD44 expression [147]. HA-coated nanoparticles containing anti-tumor drugs could also target CD44-positive cancer cells with high specialization and efficient drug delivery, refining the current anticancer management [148][149][150][151][152][153]. It has been observed that a rationally designed nanosystem containing gold nanostar/siRNA of heat shock protein 72/HA is endowed with the property of selectively sensitizing CD44-positive TNBC cells to hyperthermia, and improves the therapeutic accuracy and efficacy to TNBC with decreased unpleasant side effects both in vitro and in vivo [153].…”
Section: Cd44 and The Development Of Anti-tumor Drugsmentioning
confidence: 99%
“…Cryo-EM sample preparation and micrograph acquisition. Previously published methods were applied for sample preparation 6 . 32 .…”
Section: Characterization Of Liposomes By Electron Microscopy (Tem Ementioning
confidence: 99%
“…If the organic solvent is miscible with water, liposomes can be prepared by mixing an alcoholic solution of lipids with aqueous phase. Ethanol injection method 2 and proliposome-liposome method 2,3 represent well-established techniques used in the laboratory as well as on an industrial scale [4][5][6] .…”
Section: Introduction Of Microfluidic Mixing Technique Opens a New Domentioning
confidence: 99%
“…Several different liposomal preparations are in use as vaccines or for the treatment of infectious diseases, cancer or dermatological disorders [24][25][26]. Technologies for preparation and production of liposomes at industrial scale are available and bioconjugate chemistry for surface modifications of liposome by ligands of various chemical structure are currently being developed [27][28][29].…”
Section: Introductionmentioning
confidence: 99%